PERAN E-BOOK INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS V MATERI SIKLUS AIR - Reviani Fitri; Regina Lichteria Panjaitan; Atep Sujana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Limitations in learning media can hinder the optimization of the learning process, resulting in students not fully understanding concepts, particularly IPAS material. This study aims to test the effectiveness of interactive e-books in improving students' understanding of IPAS material, specifically related to the water cycle. A pre-experimental design with groups in a pretest-posttest format was used in this study. The study involved 30 fifth-grade students (18 boys and 12 girls) from a public elementary school in one of the sub-districts in Pamulihan. The measurement tool used was a written test to assess understanding of IPAS material on the water cycle. Data analysis involved a normality test, as the results were normal, followed by a t-test and an N-Gain test. The results of the paired t-test showed a significant difference between the pretest and posttest results (Sig. <0.05). The degree of improvement in understanding, calculated using N-Gain, was in the high category, indicating that this medium can effectively enhance students' understanding of the concept. Based on these results, the interactive electronic book on the water cycle is effective for teaching the IPAS water cycle in elementary schools.